PORTLAND CEMENT TO GET PRINCIPLE SCHEME (Multidisciplinary Journal of Science and Technology, 2024)
This document presents a concise overview of the principles underlying the manufacturing process of Portland cement, a fundamental construction material. The focus is on the key steps involved in cement production, including the extraction and preparation of raw materials, the formation of clinker through high-temperature reactions, and the subsequent grinding and packaging processes. The chemical reactions governing clinker formation are outlined, emphasizing the crucial role of calcium silicates. This annotation serves as a guide for understanding the principal scheme of Portland cement production.